Técnicas de expansión torácica en pacientes postoperatorios de cirugía abdominal. - Pastuña Bassante, Ximena Janeth (2024)
The present research work corresponds to a compilation and bibliographic review of scientific articles in the different search engines used such as: Pubmed, Scielo, Google academic, Semantic Scholar, Cochrane library and Research Gate, with the purpose of analyzing the effects of thoracic expansion techniques in postoperative abdominal surgery patients through an exhaustive search for articles of greatest impact used rigorously with the inclusion and exclusion criteria, which the methodology used was documentary type with an inductive method, qualitative level and descriptive design. Abdominal surgery is a procedure of the abdominal area, this is based on performing a surgical technique to make a large incision called open abdominal surgery or laparotomy, therefore, it is called the main source of problems in respiratory function, which triggers the appearance of pulmonary complications, increasing the risk of mortality. Currently, respiratory therapy has been invading the field of physiotherapy, among them we have thoracic expansion techniques that have gained great relevance in physiotherapy treatment, to treat respiratory pathologies post-operative abdominal surgery due to the use of these techniques there are greater benefits. regarding the improvement of respiratory efficiency such as Increasing the ventilation of the alveoli increases the strength in the respiratory muscles, thus improving lung ventilation, increasing the functional residual capacity (FRC) and broadening inhalation, in this way effort is more easily controlled. respiratory, reduces cough, expectoration, and sensation of dyspnea, improves quality of life and the ability to carry out daily activities.